A high-strength PP material and its application in GAG decorative film

By forming alumina particles on graphene oxide and forming an organic cladding layer, combined with SG copolymer, the problem of insufficient strength and thermal stability of PP materials in GAG decorative film is solved, and the mechanical properties and compatibility of the materials are significantly improved. , ensuring durability of the membrane body.

CN118791798BActive Publication Date: 2025-01-14DONGGUAN XUSHENG PLASTIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410885138.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2025-01-14
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

Existing PP materials are difficult to meet the requirements of high strength and thermal stability in GAG decorative films, and are prone to damage or tear due to external forces and environmental factors.

Method used

Using the modified filler preparation method, alumina particles are generated in situ on graphene oxide, and an organic coating layer is formed by clicking reaction of thiol succinic acid and 4-allyl catechol, combined with SG copolymer to improve Mechanical properties and compatibility of materials.

Benefits of technology

It significantly improves the mechanical properties and thermal stability of PP materials, enhances its endurance to tensile and impact, reduces graphene oxide agglomeration phenomenon, and ensures the overall performance of the film body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004925829750000081
    Figure BDA0004925829750000081
Patent Text Reader

Abstract

The present invention relates to a high-strength PP material and its application in a GAG decorative film, belonging to the technical field of PP materials. A high-strength PP material comprises the following components: polypropylene, modified filler, SG copolymer, antioxidant and light stabilizer. The SG copolymer is styrene-methacrylate glycidyl ester copolymer; the light stabilizer is a mixture of titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate. The PP material prepared by the present invention has the characteristics of excellent mechanical strength and thermal stability. When applied to a GAG decorative film, the film body is not easily damaged or torn.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PP materials and relates to a high-strength PP material and an application thereof in a GAG decorative film. Background Art

[0002] GAG decorative film is a three-layer composite film produced by co-extrusion. This film is specially coated and is particularly suitable for high-frequency heat-sealing and glue-bonded decorative building materials. The base material of GAG film has a certain flexibility, and its surface film needs to have a certain tensile strength and tear strength. During use, the decorative film may be affected by friction, ultraviolet rays, temperature changes and other factors. Polypropylene material, as one of the main materials of the film, needs to meet this requirement to ensure that the GAG ​​decorative film is not easily damaged or torn during use. Therefore, high-strength PP material is required to resist the external force that may be generated during the installation and use of GAG film.

[0003] Graphene is a two-dimensional material with hexagonal arrangement of carbon atoms. It has excellent mechanical and electrical properties, high thermal conductivity, high specific surface area and good compatibility. Therefore, it is widely used in decorative films, electronics, solar cells and electrochemical sensors, and is often used as a multifunctional nanofiller. Compared with graphene, graphene oxide has more excellent mechanical properties, compatibility and solubility. If the addition amount is too small, it cannot meet the improvement of mechanical properties. However, if the addition amount is too high, it is easy to form blocks in the system due to the agglomeration of graphene oxide itself, and the distribution is uneven, resulting in a decrease in the mechanical properties of the material. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength PP material and its application in GAG decorative film. The PP material prepared has the characteristics of excellent mechanical strength and thermal stability. When applied to GAG decorative film, the film body is not easily damaged or torn.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength PP material comprises the following components by weight: 110-120 parts of polypropylene, 10-12 parts of modified filler, 4-6 parts of SG copolymer, 1.0-1.5 parts of antioxidant and 0.6-0.8 parts of light stabilizer;

[0007] The preparation method of the modified filler comprises the following steps:

[0008] 1) In an inert atmosphere, aluminum nitrate solution and sodium hydroxide aqueous solution are added dropwise to graphene oxide, and the mixture is allowed to stand, and the solid is washed and dried in an oven to obtain composite particles;

[0009] 2) After the composite particles, anhydrous ethanol and mercaptosuccinic acid are stirred and mixed, 4-allylcatechol and an initiator are added, heated and stirred, and the solid matter is washed and placed in an oven for drying to obtain a modified filler.

[0010] As a preferred technical solution of the present invention, in step 1), the inert atmosphere is a nitrogen atmosphere; the dripping time is 1 hour; the standing time is 2-3 hours; the washing is washing with a 50% mass fraction ethanol aqueous solution; and the drying is drying at 120°C for 24-30 hours.

[0011] As a preferred technical solution of the present invention, in step 1), the mass ratio of the aluminum nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 12-14:20-23:45-50.

[0012] As a preferred technical solution of the present invention, in step 1), the aluminum nitrate solution is prepared by mixing aluminum nitrate nonahydrate and deionized water in a mass ratio of 1.0-1.2:5.0-5.5; and the concentration of the sodium hydroxide aqueous solution is 50 g / L.

[0013] As a preferred technical solution of the present invention, in step 2), the stirring and mixing is stirring at a speed of 400-500 r / min for 15-20 min; the heating and stirring is stirring at a temperature of 35-40°C for 6-8 h; the washing is washing 3 times with anhydrous ethanol; and the drying is drying at a temperature of 80°C to constant weight.

[0014] As a preferred technical solution of the present invention, in step 2), the mass ratio of the composite particles, anhydrous ethanol, mercaptosuccinic acid, 4-allylcatechol and initiator is 12-14: 50-58: 4.5-5.0: 6.0-6.3: 0.25-0.30; the initiator is ammonium cerium nitrate.

[0015] As a preferred technical solution of the present invention, the SG copolymer is styrene-glycidyl methacrylate copolymer, purchased from Jiayi Rong Compatibilizer Jiangsu Co., Ltd.; the antioxidant is antioxidant 1010; polypropylene is purchased from Nantong Runfeng Petrochemical Co., Ltd.; the light stabilizer is titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate mixed in a mass ratio of 1.5:2-2.2.

[0016] The invention discloses a preparation method of a high-strength PP material, comprising the following steps: placing an antioxidant, a light stabilizer, a modified filler and an SG copolymer in a twin-screw extruder for melt mixing, adding polypropylene for secondary melt mixing, and extruding a masterbatch to obtain a high-strength modified PP material.

[0017] As a preferred technical solution of the present invention, the temperature of the melt mixing is 180-190°C; the temperature of the secondary melt mixing is 190-210°C

[0018] The invention discloses a high-strength PP material applied to a GAG decorative film.

[0019] Beneficial effects of the present invention:

[0020] The present invention generates alumina particles in situ on graphene oxide, and then forms an organic coating layer containing a rigid benzene ring structure on the composite particles through a click reaction between mercaptosuccinic acid and 4-allylcatechol. Finally, the SG copolymer reacts with the modified filler to further increase the compatibility, thereby significantly improving the mechanical properties and thermal stability of the PP material. DETAILED DESCRIPTION

[0021] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0022] SG copolymer is styrene-glycidyl methacrylate copolymer, purchased from Jiayirong Compatibilizer Jiangsu Co., Ltd.; polypropylene was purchased from Nantong Runfeng Petrochemical Co., Ltd.; the antioxidant is antioxidant 1010.

[0023] Example 1

[0024] A high-strength PP material comprises the following components by weight: 110 parts of polypropylene, 10 parts of modified filler, 4 parts of SG copolymer, 1.0 part of antioxidant and 0.6 part of light stabilizer; the SG copolymer is styrene-glycidyl methacrylate copolymer; the light stabilizer is a mixture of titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate in a mass ratio of 1.5:2;

[0025] The preparation method of the modified filler comprises the following steps:

[0026] 1) In an inert atmosphere, aluminum nitrate solution and sodium hydroxide aqueous solution are added dropwise to graphene oxide, and the mixture is allowed to stand, and the solid is washed and dried in an oven to obtain composite particles;

[0027] In step 1), the inert atmosphere is a nitrogen atmosphere; the dropping time is 1 hour; the standing time is 2 hours; the washing is washing with a 50% mass fraction ethanol aqueous solution; the drying is drying at 65° C. to constant weight;

[0028] In step 1), the mass ratio of the aluminum nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 12:20:45;

[0029] In step 1), the aluminum nitrate solution is prepared by mixing aluminum nitrate nonahydrate and deionized water in a mass ratio of 1.0:5.0; the concentration of the sodium hydroxide aqueous solution is 50 g / L;

[0030] 2) After the composite particles, anhydrous ethanol and mercaptosuccinic acid are stirred and mixed, 4-allylcatechol and an initiator are added and heated and stirred, and the solid matter is washed and placed in an oven for drying to obtain a modified filler;

[0031] In step 2), the stirring and mixing is stirring at a speed of 400 r / min for 15 minutes; the heating and stirring is stirring at a temperature of 35° C. for 6 hours; the washing is washing with anhydrous ethanol for 3 times; and the drying is drying at a temperature of 120° C. for 24 hours;

[0032] In step 2), the mass ratio of the composite particles, anhydrous ethanol, mercaptosuccinic acid, 4-allylcatechol and initiator is 12:50:4.5:6.0:0.25; the initiator is ammonium cerium nitrate;

[0033] A preparation method of a high-strength PP material comprises the following steps: placing an antioxidant, a light stabilizer, a modified filler and an SG copolymer in a twin-screw extruder for melt mixing, adding polypropylene for secondary melt mixing, and extruding a masterbatch to obtain a high-strength modified PP material; the temperature of the melt mixing is 180°C; the temperature of the secondary melt mixing is 190°C.

[0034] Example 2

[0035] A high-strength PP material comprises the following components by weight: 115 parts of polypropylene, 11 parts of modified filler, 5 parts of SG copolymer, 1.2 parts of antioxidant and 0.7 parts of light stabilizer; the SG copolymer is styrene-glycidyl methacrylate copolymer; the light stabilizer is a mixture of titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate in a mass ratio of 1.5:2.1;

[0036] The preparation method of the modified filler comprises the following steps:

[0037] 1) In an inert atmosphere, aluminum nitrate solution and sodium hydroxide aqueous solution are added dropwise to graphene oxide, and the mixture is allowed to stand, and the solid is washed and dried in an oven to obtain composite particles;

[0038] In step 1), the inert atmosphere is a nitrogen atmosphere; the dripping time is 1 hour; the standing time is 2.5 hours; the washing is washing with a 50% mass fraction ethanol aqueous solution; the drying is drying at 120° C. for 27 hours;

[0039] In step 1), the mass ratio of the aluminum nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 13:22:48;

[0040] In step 1), the aluminum nitrate solution is prepared by mixing aluminum nitrate nonahydrate and deionized water in a mass ratio of 1.1:5.2; the concentration of the sodium hydroxide aqueous solution is 50 g / L;

[0041] 2) After the composite particles, anhydrous ethanol and mercaptosuccinic acid are stirred and mixed, 4-allylcatechol and an initiator are added and heated and stirred, and the solid matter is washed and placed in an oven for drying to obtain a modified filler;

[0042] In step 2), the stirring and mixing is stirring at a speed of 450 r / min for 18 minutes; the heating and stirring is stirring at a temperature of 38° C. for 7 hours; the washing is washing with anhydrous ethanol for 3 times; and the drying is drying at a temperature of 80° C. to constant weight;

[0043] In step 2), the mass ratio of the composite particles, anhydrous ethanol, mercaptosuccinic acid, 4-allylcatechol and initiator is 13:54:4.8:6.2:0.28; the initiator is ammonium cerium nitrate;

[0044] A preparation method of a high-strength PP material comprises the following steps: placing an antioxidant, a light stabilizer, a modified filler and an SG copolymer in a twin-screw extruder for melt mixing, adding polypropylene for secondary melt mixing, and extruding a masterbatch to obtain a high-strength modified PP material; the temperature of the melt mixing is 185°C; the temperature of the secondary melt mixing is 200°C.

[0045] Example 3

[0046] A high-strength PP material comprises the following components by weight: 120 parts of polypropylene, 12 parts of modified filler, 6 parts of SG copolymer, 1.5 parts of antioxidant and 0.8 parts of light stabilizer; the SG copolymer is styrene-glycidyl methacrylate copolymer; the light stabilizer is a mixture of titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate in a mass ratio of 1.5:2.2;

[0047] The preparation method of the modified filler comprises the following steps:

[0048] 1) In an inert atmosphere, aluminum nitrate solution and sodium hydroxide aqueous solution are added dropwise to graphene oxide, and the mixture is allowed to stand, and the solid is washed and dried in an oven to obtain composite particles;

[0049] In step 1), the inert atmosphere is a nitrogen atmosphere; the dripping time is 1 hour; the standing time is 3 hours; the washing is washing with a 50% mass fraction ethanol aqueous solution; the drying is drying at a temperature of 120° C. for 30 hours;

[0050] In step 1), the mass ratio of the aluminum nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 14:23:50;

[0051] In step 1), the aluminum nitrate solution is prepared by mixing aluminum nitrate nonahydrate and deionized water in a mass ratio of 1.2:5.5; the concentration of the sodium hydroxide aqueous solution is 50 g / L;

[0052] 2) After the composite particles, anhydrous ethanol and mercaptosuccinic acid are stirred and mixed, 4-allylcatechol and an initiator are added and heated and stirred, and the solid matter is washed and placed in an oven for drying to obtain a modified filler;

[0053] In step 2), the stirring and mixing is stirring at a speed of 500 r / min for 20 minutes; the heating and stirring is stirring at a temperature of 40° C. for 8 hours; the washing is washing with anhydrous ethanol for 3 times; and the drying is drying at a temperature of 80° C. to constant weight;

[0054] In step 2), the mass ratio of the composite particles, anhydrous ethanol, mercaptosuccinic acid, 4-allylcatechol and initiator is 14:58:5.0:6.3:0.30; the initiator is ammonium cerium nitrate;

[0055] A preparation method of a high-strength PP material comprises the following steps: placing an antioxidant, a light stabilizer, a modified filler and an SG copolymer in a twin-screw extruder for melt mixing, adding polypropylene for secondary melt mixing, and extruding a masterbatch to obtain a high-strength modified PP material; the temperature of the melt mixing is 190°C; the temperature of the secondary melt mixing is 210°C.

[0056] Comparative Example 1

[0057] Compared with Example 2, Comparative Example 1 is different in that graphene oxide is used instead of the composite particles, and the other components, preparation steps and parameters are the same.

[0058] Comparative Example 2

[0059] Compared with Example 2, Comparative Example 2 is different in that phenylpropene is used instead of 4-allylcatechol, and the other components, preparation steps and parameters are the same.

[0060] Comparative Example 3

[0061] Compared with Example 2, Comparative Example 3 is different in that 4-allylcatechol is not used, and the other components, preparation steps and parameters are the same.

[0062] Comparative Example 4

[0063] Compared with Example 2, Comparative Example 4 is different in that step 2) is not performed, and the remaining components, preparation steps and parameters are the same.

[0064] Comparative Example 5

[0065] Compared with Example 2, Comparative Example 5 is different in that no SG copolymer is used, and the other components, preparation steps and parameters are the same.

[0066] The PP materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested as follows, and the test results are shown in Table 1.

[0067] Tensile strength test: Sample size: 12cm×4cm×0.4cm; According to GB / T 1040.1-2018 standard, the tensile properties are tested by a universal material testing machine with a tensile rate of 50mm / min.

[0068] Charpy notched impact strength test: GB / T 1043.1-2008, measuring injection molded samples at 23°C.

[0069] Heat Deformation Temperature: Measure injection molded samples according to GB / T 1634.2-2004.

[0070] Table 1 Tensile strength, impact strength and heat deformation temperature test

[0071]

[0072] From the test results in Table 1, it can be seen that compared with comparative examples 1-5, the tensile strength and simply supported beam notched impact strength of the PP material prepared in Examples 1-3 of the present invention are high, and the PP material has excellent mechanical properties. Analysis shows that the present invention generates aluminum oxide particles in situ on graphene oxide to reduce the self-agglomeration phenomenon of graphene oxide, improves the mechanical properties of the PP material, and improves its thermal stability. Then, through the hydrogen bonding and coupling between mercaptosuccinic acid and the composite particles, mercaptosuccinic acid is loaded on the composite particles. Through the click reaction between 4-allyl catechol and the thiol on mercaptosuccinic acid, a hydrophobic benzene ring structure is introduced, which improves the mechanical properties of the material and increases its compatibility in the PP system. The two hydroxyl groups of 4-allyl catechol increase the coverage rate through hydrogen bonding and electrostatic action, and generate an organic coating layer with high binding force on the surface of the composite particles. Finally, the SG copolymer reacts with the hydroxyl and carboxyl groups in the modified filler to further increase its compatibility in the PP material system, significantly improving the mechanical properties and thermal stability of the PP material.

[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high-strength PP material, characterized in that: The following components are included by weight: 110-120 parts of polypropylene, 10-12 parts of modified filler, 4-6 parts of SG copolymer, 1.0-1.5 parts of antioxidant and 0.6-0.8 parts of light stabilizer; The preparation method of the modified filler comprises the following steps: 1) In an inert atmosphere, aluminum nitrate solution and sodium hydroxide aqueous solution are added dropwise to graphene oxide, and the mixture is allowed to stand, and the solid is washed and dried in an oven to obtain composite particles; 2) After the composite particles, anhydrous ethanol and mercaptosuccinic acid are stirred and mixed, 4-allylcatechol and an initiator are added, heated and stirred, and the solid matter is washed and placed in an oven for drying to obtain a modified filler.

2. A high-strength PP material according to claim 1, characterized in that: In step 1), the inert atmosphere is a nitrogen atmosphere; the dropping time is 1 hour; the standing time is 2-3 hours; the washing is performed by washing with a 50% by mass ethanol aqueous solution; and the drying is performed at 120° C. for 24-30 hours.

3. The high-strength PP material according to claim 1, characterized in that: In step 1), the mass ratio of the aluminum nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 12-14:20-23:45-50.

4. The high-strength PP material according to claim 1, characterized in that: In step 1), the aluminum nitrate solution is prepared by mixing aluminum nitrate nonahydrate and deionized water in a mass ratio of 1.0-1.2:5.0-5.5; the concentration of the sodium hydroxide aqueous solution is 50 g / L.

5. The high-strength PP material according to claim 1, characterized in that: In step 2), the stirring and mixing is stirring at a speed of 400-500 r / min for 15-20 min; the heating and stirring is stirring at a temperature of 35-40° C. for 6-8 h; the washing is washing 3 times with anhydrous ethanol; and the drying is drying at a temperature of 80° C. to constant weight.

6. The high-strength PP material according to claim 1, characterized in that: In step 2), the mass ratio of the composite particles, anhydrous ethanol, mercaptosuccinic acid, 4-allylcatechol and initiator is 12-14: 50-58: 4.5-5.0: 6.0-6.3: 0.25-0.30; the initiator is ammonium cerium nitrate.

7. The high-strength PP material according to claim 1, characterized in that: The SG copolymer is a styrene-glycidyl methacrylate copolymer; the light stabilizer is a mixture of titanium dioxide and 2,2,6,6-tetramethyl-4-piperidinyl stearate in a mass ratio of 1.5:2-2.

2.

8. The high-strength PP material according to claim 1, characterized in that: The preparation method of the high-strength PP material comprises the following steps: placing an antioxidant, a light stabilizer, a modified filler and an SG copolymer in a twin-screw extruder for melt mixing, adding polypropylene for secondary melt mixing, and extruding a masterbatch to obtain a high-strength modified PP material.

9. A high-strength PP material according to claim 8, characterized in that: The temperature of the melt mixing is 180-190°C; the temperature of the secondary melt mixing is 190-210°C.

10. An application of the high-strength PP material according to any one of claims 1 to 9, characterized in that: The high-strength PP material is applied to the GAG ​​decorative film.

Citation Information

Patent Citations

  • Self-lubricating anti-abrasion polypropylene composite material and preparation method and application thereof

    CN108285584A

  • Lithium ion battery shell

    CN113773578A